Stage-specific milk yield losses and associated sweating, respiration, and rectal temperature responses under varying temperature-humidity index thresholds in lactating and dry cows - P.A. Tu; Y.H. Yeh; Y.H. Chen; J.W. Shiau; T.Y. Lin; Thomas Banhazi; M.K. Yang (Journal of Dairy Science)
ABSTRACT: Heat stress (HS) may result in changes in the behavior, endocrine system, and physiological characteristics of dairy cows, and it may even lead to death in severe cases. As the effects of global warming have become more notable, the prevalence of HS has increased among dairy cows. Therefore, comprehensive strategies, including not only cooling measures but also dietary adjustments and genetic improvements for heat tolerance, are required to help these animals regulate their body temperature and avoid HS. In addition, detecting HS signs is essential for both lactating and dry cows to ensure appropriate interventions. The temperature-humidity index (THI) is a widely used tool for evaluating the effects of HS on livestock. Because the physiological state of cattle significantly influences their responses to HS, it is imperative to establish specific THI thresholds for both lactating and dry cows to implement appropriate cooling regimens and optimize animal welfare. In this study, we used the THI to investigate the relationship between rectal temperature (RT), respiration rate (RR), and sweating rate (SR) in lactating and dry cows. We also explored the relationships between milk yield at different lactation stages and THI thresholds. The results indicated that lactating and dry cows had different THI thresholds based on their immediate physiological responses. Compared with lactating cows, dry cows had higher THI thresholds for RT, RR, and SR. In addition, cows in early-, intermediate-, and late-lactation stages under thermoneutral conditions produced significantly more milk than did those under mild, moderate, and severe HS conditions, indicating that milk yield losses occur under HS conditions. Taken together, these findings provide valuable insights into how HS can be mitigated in subtropical dairy farms. For lactating cows, implementing cooling measures is recommended when the THI reaches 66 to 67, whereas for dry cows, waiting until the THI reaches 73 is recommended. Milk yield losses may occur when lactating cows are under HS conditions. Therefore, appropriate cooling measures should be implemented at accurate THI thresholds to ensure optimal animal welfare for both lactating and dry cows.